Peran Employee Relationship Proneness Terhadap Sikap Dan Perilaku Loyalitas Karyawan Rumah Sakit Islam Ibnu Sina Pekanbaru - khairani, zulia (Jurnal Daya Saing, 2016)
Abstract: This study is aimed at understanding and discovering the influence of employee relations towards the loyalty attitude dimension. Furthermore, It also attempts to find out and comprehend the impact of loyalty attitude dimension of employee on each of the dimension. The data of this research was gathered by mean of questionnaires which were delivered to 130 respondent selected using purposive sampling. Structural Equation Modeling (SEM) had been used as the main analysis technique. The result of this study demonstrates that the tendency of employee relation has a significant positive role in building effective commitment. Conversely, it does not show any significant positive role on both calculative and normative commitment. In addition, It is also observed that affective commitment has only positive significant role in building intention to stay attitude. Meanwhile, calculative and normative commitment have resulted in insignificant positive role towards intention to stay. Each of the loyalty attitude dimensions; affective, calculative and normative commitments have no significant role towards positive variable dimensions (WOM), insensitivity towards benefit and complain. Keywords: Employee Relationship Proneness, attitude, behavior, loyality.